Use of E-Learning System in Technology Acceptance Model (TAM) on Accredited PTS Students in BAN-PT Bandung - Nurhayati, Nunung; Fitriah, Epi; ., Diamonalisa; Halimatusadiah, Elly; Azis, Rayhan; ., Helliana; ., Khalid (KnE Social Sciences, 2023)
E-learning is an application utilized to support the teaching and learning process at a private university in Bandung City during the Covid-19 pandemic. The users of E-learning comprise lecturers and students. However, no evaluation has been conducted regarding the user acceptance of the E-learning system employed. This study aims to determine the factors of the Technology Acceptance Model (TAM), namely Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Intention to Use (ITU), and Attitude Towards Using (ATU), on the acceptance of the E-learning system. The research employs descriptive analysis and verification as the research methods. The research population consists of university students in the city of Bandung, whose universities have been accredited by BAN-PT and already utilize the E-Learning system. Convenient sampling is used, and 260 student respondents from 12 private universities in Bandung using E-Learning are included in the sample. Data analysis is conducted using Structural Equation Model (SEM). The study's results demonstrate that Perceived Usefulness (PU) has a positive impact on intention. Perceived Ease of Use (PEOU) significantly affects Intention to Use (ITU), and Attitude towards Using (ATU) positively influences the utilization of E-Learning applications among students in private universities in Bandung. Keywords: perceived usefulness, perceived ease of use, intention to use, e-learning